Biological removal of phosphorus and nitrogen from wastewater : new insights from metagenomic and metatranscriptomic approaches - Mao, Yanping (The University of Hong Kong (Pokfulam, Hong Kong), 2014)
abstract === Civil Engineering === Doctoral === Doctor of Philosophy